The Clinical and Pathological Effects of Serum C3 Level and Mesangial C3 Intensity in Patients with IgA Nephropathy - Xiaoyue Hou; Yanan Liang; Weiwei Zhang; Rong Li (Analytical Cellular Pathology)
Objective. To investigate the clinical and pathological effects of serum C3 level, mesangial C3 deposition intensity and blood lipid on IgA nephropathy. Methods. According to the deposition intensity of immunofluorescence (IF) complement C3 in mesangial region, a total of 151 patients were divided into: (1) negative group (65 cases), (2) weak positive group (51 cases), and (3) strong positive group (35 cases). According to the level of serum C3, the patients were divided into two groups: (1) 33 patients with decreased serum C3 (<85 mg/dL); (2) 118 patients with normal serum C3. The clinicopathological data of the patients were analyzed retrospectively according to the groups. Results. (1) With the increase of C3 deposition in mesangial region, the mean value of serum C3 level decreased, and the difference was statistically significant (P=0.001). (2) Compared with the normal serum C3 group, the blood urea nitrogen (BUN), serum creatinine (Scr), and albumin (Alb) in the serum C3 decreased group were higher, and the differences were statistically significant (P<0.05), while the fasting blood glucose (FBG), low-density lipoprotein (LDL), triglyceride and 24-hr urinary protein (24hUTP) were lower, which difference was statistically significant (P<0.05). (3) Compared with negative group and weak positive group, BUN, uric acid (UA), and Scr were higher in the strong positive group with C3 deposition, while eGFR was lower, with statistical significance (P<0.05). However, C3 deposition in the mesangial region was related to T and enhanced mesangial C3 deposition was associated with more severe tubular atrophy and/or interstitial fibrosis, with statistically significant differences (P=0.001). Conclusion. Patients with strong mesangial C3 deposition and elevated lipid levels had more severe tubule atrophy and/or interstitial fibrosis, as well as more severe pathological lesions, suggesting that activation of the complement system is involved in the pathogenesis of IgA nephropathy and increases the metabolic burden of the kidney.